Pengaruh Motivasi Dan Disiplin Belajar Terhadap Prestasi Belajar Pada Mata Pelajaran IPS Kelas VIII di UPTD SMP Negeri 7 Pematang Siantar - Karlos Immanuel Sibuea; Injen Pardamean Butar-butar; Tumpal Manahara Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
The problem in this research is that student discipline in general is still relatively low which can be seen in terms of not bringing learning equipment, not completing assignments on time, not completing homework on time, not entering class on time. This research aims to find out how much influence motivation and discipline have on the social studies learning achievement of class VIII UPTD students at SMP Negeri 7 Pematang Siantar for the 2022/2023 academic year. This type of research is quantitative research carried out at SMP Negeri 7 Pematang Siantar. The population in this study were all students in class VIII of SMP Negeri 7 Pematang Siantar, totaling 223 students. The sample in this study consisted of 7 classes, namely classes VIII-1 to VIII-7 with a total of 146 students. Data analysis techniques are carried out in several stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of the classical assumption test, the above normality test is the main requirement to be able to proceed to the multiple regression analysis test with the data having a normal distribution and a significance level of > 0.05. The t test results are based on table 4.8. The calculated t value of motivation (2.544) is greater than the t table (1.6553). Based on the results obtained, we accept Ha and accept H0 for the motivation variable. Thus, there is an influence between motivation on the learning achievement of class VIII UPTD students at SMP Negeri 7 Pematang Siantar. The calculated t value of learning discipline (2.997) is greater than the t table (1.6553), so based on the results obtained, we accept Ho and accept Ha for the learning discipline variable. Thus, learning discipline partially influences the learning achievement of class VIII UPTD students at SMP Negeri 7 Pematang Siantar. So it can be concluded that self-efficacy and the school environment jointly influence student learning achievement, this result can be seen in the F test where the Fcount value (11.526) > Ftable value (2.6678). The R Square coefficient of determination test was found to be 0.139, which means that 13.9% of the motivation and learning discipline variables influence student learning achievement at the UPTD SMP Negeri 7 Pematang Siantar school. Meanwhile, 86.1% is the influence of other variables not examined in this research, such as self-confidence, interest in learning, and peers.